0.16(y-2)+0.12y=0.20y-0.7

Simple and best practice solution for 0.16(y-2)+0.12y=0.20y-0.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.16(y-2)+0.12y=0.20y-0.7 equation:


Simplifying
0.16(y + -2) + 0.12y = 0.20y + -0.7

Reorder the terms:
0.16(-2 + y) + 0.12y = 0.20y + -0.7
(-2 * 0.16 + y * 0.16) + 0.12y = 0.20y + -0.7
(-0.32 + 0.16y) + 0.12y = 0.20y + -0.7

Combine like terms: 0.16y + 0.12y = 0.28y
-0.32 + 0.28y = 0.20y + -0.7

Reorder the terms:
-0.32 + 0.28y = -0.7 + 0.20y

Solving
-0.32 + 0.28y = -0.7 + 0.20y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.20y' to each side of the equation.
-0.32 + 0.28y + -0.20y = -0.7 + 0.20y + -0.20y

Combine like terms: 0.28y + -0.20y = 0.08y
-0.32 + 0.08y = -0.7 + 0.20y + -0.20y

Combine like terms: 0.20y + -0.20y = 0.00
-0.32 + 0.08y = -0.7 + 0.00
-0.32 + 0.08y = -0.7

Add '0.32' to each side of the equation.
-0.32 + 0.32 + 0.08y = -0.7 + 0.32

Combine like terms: -0.32 + 0.32 = 0.00
0.00 + 0.08y = -0.7 + 0.32
0.08y = -0.7 + 0.32

Combine like terms: -0.7 + 0.32 = -0.38
0.08y = -0.38

Divide each side by '0.08'.
y = -4.75

Simplifying
y = -4.75

See similar equations:

| x^2-17X+3=0 | | 5x+43-2(x-7)=88-2x | | 8x^4+10x^3-14x^2-4x=0 | | 6x-3x=4x-1 | | y=4xn | | 2x^2-196-70x=0 | | 2y=.5x+6 | | x^3-klnx=0 | | x^3-klx=0 | | 2x-12=5x-43 | | 8x-5=2x-4.5 | | y=4x^2(5x-8) | | -8x^2+35x+-38=0 | | 1x+7=x+14 | | 22y=8y-98 | | 18x=150 | | 5y-9y=-14(-14) | | 8-x=4-.5x | | 12x+6=2x+26 | | 4x+50=13x-59 | | 0.50x+0.45(70)=34.5 | | 20y-20+20y=8y-100 | | 24x+7=30x-4 | | 3n+n-5+6= | | 3(1-2x)-5(3x)-6(3x-4)=83 | | 4+9=5 | | 28y=32y+2 | | 32+6x=12-8.5 | | -5a+12+7a=2a-4a | | x^3-4x^2-14x-14=0 | | 9x+7=-38 | | 3a+7=b |

Equations solver categories